2009
DOI: 10.1002/esp.1860
|View full text |Cite
|
Sign up to set email alerts
|

Topographic thresholds for plant colonization on semi‐arid eroded slopes

Abstract: Soil erosion plays an important role in plant colonization of semi-arid degraded areas. In this study, we aimed at deepening our knowledge of the mechanisms that control plant colonization on semi-arid eroded slopes in east Spain by (i) determining topographic thresholds for plant colonization, (ii) identifying the soil properties limiting plant establishment and (iii) assessing whether colonizing species have specifi c plant traits to cope with these limitations.Slope angle and aspect were surrogates of erosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
70
0
4

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(78 citation statements)
references
References 47 publications
(62 reference statements)
4
70
0
4
Order By: Relevance
“…The role of erosion as an ecological driver that shapes the composition of plant communities had already been highlighted in previous studies in arid and semiarid environments (Guàrdia et al, 2000;GuerreroCampo andMontserrat-Martí, 2000, 2004;García-Fayos and Bochet, 2009;Bochet et al, 2009;Jiao et al, 2009). However, relatively little attention had been paid to the effect of erosion on seeds (mainly seed transport and germination) as compared to later stages of the plant life (seedlings and adult plants; de Luís et al, 2005;Tsuyuzaki and Haruki, 2008;Wang et al, 2014), even though seed stage is one of the most critical phases in vegetation development (García-Fayos and Cerdà, 1997).…”
Section: Seed Characteristicsmentioning
confidence: 75%
See 1 more Smart Citation
“…The role of erosion as an ecological driver that shapes the composition of plant communities had already been highlighted in previous studies in arid and semiarid environments (Guàrdia et al, 2000;GuerreroCampo andMontserrat-Martí, 2000, 2004;García-Fayos and Bochet, 2009;Bochet et al, 2009;Jiao et al, 2009). However, relatively little attention had been paid to the effect of erosion on seeds (mainly seed transport and germination) as compared to later stages of the plant life (seedlings and adult plants; de Luís et al, 2005;Tsuyuzaki and Haruki, 2008;Wang et al, 2014), even though seed stage is one of the most critical phases in vegetation development (García-Fayos and Cerdà, 1997).…”
Section: Seed Characteristicsmentioning
confidence: 75%
“…According to all these results, it was concluded that seed loss by overland flow was not the key factor explaining the absence of vegetation on badland slopes as the probability of rainfall events of higher intensity and duration is low. Other possible alternative causes were suggested and further investigated, such as scarce water availability for plants, high salinity and the interaction of these latter factors with seed germination Bochet et al, 2009).…”
Section: Conceptual Model Of Seed Fates and Movements In And On The Soilmentioning
confidence: 99%
“…Bochet et al (2009) investigated topographic thresholds (slope angle and aspect) for plant colonization on semiarid eroded slopes in Spain, and observed that the slope angle threshold for plant colonization decreased from north-facing slopes (63°) to south-facing slopes (41°). Variations in slope angle threshold values between slope aspects resulted from differences in the colonization capacity of plants and was controlled by water availability, which was in turn controlled only by the solar radiation received (and not by soil hydrological properties).…”
Section: Topographymentioning
confidence: 99%
“…South-facing slopes accentuate the natural aridity in Mediterranean regions (Lansiart & Odent, 1999). The colonization of plants varies in the northern hemisphere, from north to south (Bochet et al, 2009). North-facing slopes are wetter, and their soils are characterized by greater organic matter content (Poesen et al, 1998;Kutiel & Lavee, 1999;Hammada et al, 2004).…”
Section: Factors For Suitability Assessment:-mentioning
confidence: 99%